Penggunaan Metode Bermain Kartu Soal Untuk Meningkatkan Kemampuan Siswa Dalam Mengerjakan Soal Cerita Pada Mata Pelajaran Matematika Bagi Siswa Kelas VI SD Negeri 22 Kepahiang Tahun Pelajaran 2020/2021 - Husin Husin (UNIVED Press, Universitas Dehasen Bengkulu, 2025)
Classroom action research aims descriptively to determine the effect of the question card playing method on improving the ability to work on story problems in class VI mathematics at SD Negeri 22 Kepahiang in 2020/2021. The hypothesis in this study is